Impedance/modulus analysis of sol-gel BaxSr1-xTiO3 thin films - Saif, Ala'eddin A.; Poopalan, Prabakaran, Assoc. Prof. (Korean Physical Society, 2011)
Link to publisher's homepage at http://www.kps.or.kr/